Persespsi Guru Terhadap Media Pop-Up Book Pada Materi Bangun Ruang Kelas V SDN Tanjungsari - Ripa Nurul Padilah; Andi Nurrochmah; Din Azwar Uswatun (Universitas Negeri Makassar, 2020)
This research is a qualitative study aimed to describe the teacher's perception of pop-up book media when applied to the material building space in the V grade elementary school. The research method of using qualitative descriptive with the research data source is the teacher of grade V in elementary school Tanjungsari, namely VA and VB. The data collection techniques used are online interviews through the WhatsApp app. Data analysis techniques using the technical of Miles and Huberman are data reduction, data presentation, and withdrawal of conclusions. The result of this study raises positive perceptions of class V teachers. The Media pop-up book is interesting to apply to material solid figure in class V, seeing students who are always interested in new things, because this media has not been used, so that the media pop-up book is very good to be applied in class V, in order to support the creativity of students, so that students will be happy and think critically in the process of learning math material solid figure.